Conceptual Framework for Personal Recovery in Patients With Acute Myocardial Infarction - Rachel P. Dreyer; Anthony J. Pavlo; Anna Horne; Robert Dunn; Karina Danvers; John Brush; Mike Slade; Larry Davidson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Although there has been movement in cardiology to advance patient‐centered approaches to postacute myocardial infarction (AMI) care, work remains to be done in aligning patient preferences with clinical care. Our objective was to characterize patients’ experience of AMI and treatment to develop a new conceptual framework of patient‐centered recovery in cardiology. Methods and Results We conducted in‐depth interviews with people who previously experienced an AMI (2016–2019). The interview focused on participants’ experiences of their recovery, which were audio‐recorded, transcribed verbatim, and analyzed using a phenomenological framework. The overarching theme described by the 42 participants was feeling like a “different person” after the AMI. This shift manifested itself in both losses and gains, each of which posed new challenges to everyday life. The experience appeared to be an active process requiring people to take responsibility for their health. In terms of loss, participants describe how the AMI threatened their sense of safety and security and led to social isolation, fragility, uncertainty about the future, and difficulty expressing emotions accompanied this new fear. A conceptual framework describing the relationship between AMI, identity change, and functioning was developed. Conclusions Participants experienced the AMI as an unexpected disruption in their lives that had far‐reaching effects on their daily functioning, and were resolved in numerous ways. The conceptual framework may assist in providing a theoretical basis for future interventions in cardiology that not only engage and retain patients in care but also improve long‐term adherence to secondary prevention and other aspects of self‐care.